Evaluation of Critical Limit of Iron in Aridisols for Wheat - Gupta, V K; Potalia, B S (Annals of Arid Zone, 2016)
The DTPA extractable Fe in 19 surface soils of arid region of Haryana. ranged from 1.4 to 6.4 ppm. A response of less than 10 per cent was obtained in 42 per cent soils while 58 per cent soils gave a response of more than 10 per cent. Soils having less than 3.2 ppm DTPA extractable Fe were highly responsive to Fe application. Bray's per cent yield ranged from 44.5 to 103.7 and was significantly and positively correlated with DTPA Fe (r = 0.75). The critical DTPA extractable Fe concentration in soil below which wheat will respond to Fe application was found to be 4.0 ppm.